2022
DOI: 10.1038/s41598-022-25083-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic enhancement of the one carbon metabolism (OCM) in bovine oocytes IVM increases the blastocyst rate: evidences for a OCM checkpoint

Abstract: The one carbon metabolism (OCM) has a primary role in the process of oocyte maturation. In this study bovine oocytes were cultured for 24 h, up to MII stage, with standard medium supplemented or not with 8 metabolic enhancers of the OCM and the MII and blastocyst rate were compared. Additional analyses were performed on matured oocytes, cumulus cells, zygotes and blastocysts. The OCM supplementation increased the blastocyst rate derived from in vitro fertilization. The mitochondrial mass and DNMT3a protein exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
(61 reference statements)
0
1
1
Order By: Relevance
“…In spite of no detectable differences in oocyte number, maturation and fertilization, the zygotes from supplemented follicles resulted in a blastocyst rate that was almost double the one in their controls. Our experimental model does not allow to infer on the reasons for this difference; however, these findings overlap with the one resulting from a recent study based on the use of comparable amounts of the same micronutrients supplemented during the 24-h in vitro maturation of bovine oocytes [ 23 ]. Also, in this case, after overlapping maturation and fertilization rate, the supplemented oocytes exerted a double blastocyst rate as compared to their controls (32.5% vs 15.7%; p < 0.001).…”
Section: Discussioncontrasting
confidence: 68%
“…In spite of no detectable differences in oocyte number, maturation and fertilization, the zygotes from supplemented follicles resulted in a blastocyst rate that was almost double the one in their controls. Our experimental model does not allow to infer on the reasons for this difference; however, these findings overlap with the one resulting from a recent study based on the use of comparable amounts of the same micronutrients supplemented during the 24-h in vitro maturation of bovine oocytes [ 23 ]. Also, in this case, after overlapping maturation and fertilization rate, the supplemented oocytes exerted a double blastocyst rate as compared to their controls (32.5% vs 15.7%; p < 0.001).…”
Section: Discussioncontrasting
confidence: 68%
“…Thus, our results completely align with the previously reported finding. In addition, it has been shown that the addition of one-carbon metabolism (OCM) enhancers during oocyte maturation significantly increased oocyte mitochondrial mass, DNMT3A protein expression, and blastocyst rate, possibly due to improved epigenetic programming [30]. OCM consists of three related pathways: the folate and methionine cycles, and the trans-sulphuration pathway [30].…”
Section: Discussionmentioning
confidence: 99%